Investigations on age, growth and mortality parameters of Ailia coila (Hamilton, 1822) (Siluriformes: Ailiidae) from Brahmaputra river system of Assam, India - Gogoi, Pranab; Ahirwal, Surendra Kumar; Chakraborty, Sushant Kumar; Bhattacharjya, B K; Jaiswar, Ashok Kumar; Singh, Jaspreet; Behera, Prajna Ritambhara (Indian Journal of Fisheries, 2021)
The present study deals with the detailed investigation on population dynamics of the near-threatened catfish Ailia coila(Hamilton, 1822), which inhabits the Brahmaputra River of India and forms an important component of freshwater inlandfishery, providing nutritional and financial security to the local community. A total of 1034 individuals were collected byweekly sampling from the Uzanbazar and Dhubri landing centres of this river system from September 2013 to April 2014.The estimated asymptotic length (Lâˆž), growth coefficient (K) and age at zero length (t0) of A. coila were 268 mm, 0.87 yr-1and t0 = 0.000028 years respectively. Estimated total mortality (Z), natural mortality (M) and fishing mortality coefficient(F) were 5.76, 1.63 and 4.13 yr-1 respectively. Using von Bertalanffy growth formula (VBGF) the length attained at the endof first, second and third years of life were estimated at 156, 221 and 248 mm, respectively. The von Bertalanffy growthequation of this fish can be written as Lt = 268 {1-e-0.87(t+0.000027866)}. The exploitation ratio (U) and exploitation rate (E) andM/K ratio were estimated at 0.71, 0.72 and 1.87, respectively.Keywords: Ailia coila, Asymptotic length, Fishing mortality, Growth co-efficient, M/K ratio